Clinical characteristics and long-term outcomes related to sputum eosinophilia in Korean asthmatics - Jung, Jae-Woo (Asia Pacific Association of Allergy, Asthma and Clinical Immunology, 2011)
BACKGROUND: Bronchial asthma is usually associated with high sputum eosinophil levels. However, recent reports have suggested the importance of noneosinophilic asthma (NEA) as a distinct phenotype of asthma. OBJECTIVE: The aim of this study was to evaluate clinical significance of sputum eosinophilia and long-term treatment outcomes related to sputum eosinophilia in Korean asthmatics. METHODS: A total of 201 steroid-naive asthmatics who had undergone induced sputum analysis at baseline were selected from the Cohort for Reality and Evolution of Adult Asthma study population. Clinical evaluation, spirometry, a skin-prick test, a methacholine bronchial provocation test, and sputum eosinophil analysis were performed initially, and patients received the treatment recommended by the Global Initiative for Asthma. Lung function was evaluated every 6 months, and 53 patients completed 24 months of regular follow-up visits. Sputum eosinophilia was defined as a sputum eosinophil count of >3%. RESULTS: Of the 201 steroid-naive asthmatics, 97 patients had NEA and 104 had eosinophilic asthma (EA). Only 52% of steroid-naive asthmatic subjects had elevated baseline sputum eosinophil levels. A higher percentage of sputum eosinophils was associated with a lower PC20 (r = -0.193; p = 0.009, Spearman correlation), but not with forced expiratory volume in one second (FEV1) (r = 0.045; p = 0.525). During the 24-month study period, the percentage change of FEV1 was significantly lower in the NEA group than in the EA group at 6, 12, 18, and 24 months (p < 0.05). The NEA group, unlike the EA group, showed no significant improvement in FEV1 at 6, 12, 18, or 24 months (p > 0.05). CONCLUSION: A higher sputum eosinophil percentage was correlated with a higher airway hyperresponsiveness. Compared with EA patients, NEA patients had poor treatment outcomes in the 2-year follow-up of a Korean asthma cohort population.